Principal-Teacher Communication in Curriculum Development - Putri Barkah; Edi Harapan; Yessi Fitriani (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examines principal-teacher communication in curriculum development, focusing on: communication patterns used by the principal, teachers’ roles in planning, implementing, and evaluating the curriculum, and the relationship between communication quality and teacher participation motivated by uneven teacher involvement in Merdeka Curriculum development despite existing communication channels. A descriptive qualitative design with an axiological orientation was employed to examine ethical, normative, and practical values reflected in principal-teacher communication. Data were collected through interviews, observation, and documentation involving eight informants: the principal, vice principal for curriculum, administrative staff, and five teachers. Analysis followed reduction, display, conclusion drawing, and verification. Findings reveal combinative communication integrating formal channels (coordination meetings, supervision) and informal channels (personal discussions, WhatsApp groups). However, dialogue openness was unevenly experienced, and follow-up on teacher input required strengthening. Teachers participated in planning, implementation, and evaluation, but engagement varied some demonstrated initiative in literacy, religious, and character-building activities, while others awaited direct instruction. This study uniquely integrates axiological analysis with communication patterns in curriculum development within the Merdeka Curriculum context. Clear, open, appreciative, and consistently followed-up communication strengthens teacher participation and supports collaborative curriculum development. This research contributes empirical evidence that communication quality, reinforced through interpersonal trust, Leader-Member Exchange, and intrinsic motivation, is pivotal for fostering equitable teacher engagement in curriculum reform, offering actionable insights for primary school leaders.